(untitled) (International Journal of Biology and Chemistry, 2014)
Biologically and genetically consequences of radiation action. Consequences which emanation influence causes in a live organisms in particular could be classified by different ways depending mainly from the size of received doze. These consequences of radiation we shall enumerate in following order: changes in somatic cells leading to cancer appearance; genetic mutations rendering influence on future generations; influence on germ and fetus as a consequence of mother’s radiation during period of pregnancy; death exactly at moment of radiation. Biological consequences are: changes in organism’s cells leading to cancer appearance and mutations in sexual cells rendering influence on future generations. They are the most frequently connected with situation when huge number of people are influenced by small doses of radiation during expositions at medical aims or as a result of work on atomic electricity stations. Influence of radiation on developing germs or fruit presents itself special case worth of special discussion.